Three-dimensional elemental imaging of Li-ion solid-state electrolytes using fs-laser induced breakdown spectroscopy (LIBS). Issue 11 (12th August 2015) - Hou, Huaming; Cheng, Lei; Richardson, Thomas; Chen, Guoying; Doeff, Marca; Zheng, Ronger; Russo, Richard; Zorba, Vassilia
Abstract : We demonstrate a new way for direct 3D chemical imaging of Li-ion battery solid-electrolytes by combining femtosecond-LIBS with advanced visualization protocols. Abstract : Direct chemical imaging is critical to understand and control processes that affect the performance and safety of Li-ion batteries. In this work, femtosecond-Laser Induced Breakdown Spectroscopy (fs-LIBS) is introduced for 3D chemical analysis of Li-ion solid state electrolytes in electrochemical energy storage systems. Spatially resolved chemical maps of major and minor elements in solid-state electrolyte Li7 La3 Zr2 O12 (LLZO) samples are presented, with a depth resolution of 700 nm. We implement newly-developed visualization techniques to chemically image the atomic ratio distributions in a LLZO solid state electrolyte matrix. Statistical analysis, 2D layer-by-layer analysis, 2D cross-sectional imaging and 3D reconstruction of atomic ratios are demonstrated for electrolyte samples prepared under different processing conditions. These results explain the differences in the physical properties of the samples not revealed by conventional characterization techniques, and demonstrate the ability of fs-LIBS for direct 3D elemental imaging of Li-ion battery solid-state electrolytes.